A method and application for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membranes
By using cross-linking technology of carboxymethyl chitosan, natural collagen, proanthocyanins and sodium tripolyphosphate, the molecular structure of chitosan/collagen-based oil-water separation membrane is optimized, and its mechanical properties and stability are insufficient. The problem is that efficient oil-water separation and thermal stability are achieved, and is suitable for oil-containing wastewater treatment in the food industry.
Patent Information
- Application Number
- CN202411084965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing chitosan/collagen-based oil-water separation membrane has weak mechanical properties and poor structural stability, which limits its promotion and application in the food industry.
Using molecular crosslinking technology of carboxymethyl chitosan, natural collagen, natural crosslinking agent proanthocyanins and sodium tripolyphosphate, the molecular structure and physical and chemical properties of chitosan/collagen-based nanofiber gel are optimized, and the molecular structure and physical and chemical properties of chitosan/collagen-based nanofiber gel are constructed with Oil-water separation membrane with high mechanical properties and structural stability.
It significantly improves the mechanical properties and structural stability of the chitosan/collagen-based oil-water separation membrane, improves the porosity and crosslinking degree, improves the thermal stability and antibacterial properties of the membrane, and meets the treatment of oil-containing wastewater in the food industry. need.
Smart Images

Figure CN118846851B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of food biomaterials, and in particular to a method and application for improving the mechanical properties and structural stability of a chitosan / collagen-based oil-water separation membrane. Background Art
[0002] A large amount of oily wastewater is generated during the food industry processing. Direct discharge can easily cause problems such as drainage system blockage and environmental pollution. At present, the food processing industry mainly treats oily wastewater by gravity separation, centrifugal separation, flocculation and other methods. There are disadvantages such as high operating costs, complex equipment, high energy consumption, and secondary pollution, which limit its application in practice. In recent years, with the development of materials science, a method of separating oil-water mixtures by physically blocking water or oil using the principle of molecular sieves has attracted much attention; this method has become the mainstream direction for treating oily wastewater in the food industry due to its advantages such as wide sources of raw materials, low comprehensive cost, and efficient and convenient use. At present, the materials used in oil-water separation membranes mainly include composite membranes formed by petroleum-based polymers such as polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polypropylene (PP), nylon (PA), polysulfone (PSF) and polyethersulfone (PES). The non-degradability and difficulty of recycling of such materials themselves will also cause secondary harm to the environment, which is not in line with the current concept of green and sustainable development.
[0003] Biomass-based oil-water separation membranes have attracted great social attention due to their advantages such as biodegradable raw materials, low preparation cost, and green and environmentally friendly materials. Currently, the most studied are cellulose-based oil-water separation membranes, which have great application potential due to their advantages such as large specific surface area, high porosity, and good separation efficiency. Chitosan (CS), as the second largest natural polymer, has abundant reserves and is another ideal material for the preparation of bio-based oil-water separation membranes. The charge carried by the amino group of CS molecules acts on the microbial cell membrane, which can cause an imbalance of charge inside and outside the microbial cells, causing cell rupture and killing bacteria. Therefore, CS molecules have excellent antibacterial properties and are ideal raw materials for the development of biomass-based oil-water separation membranes. Zakuwan et al. used CS and collagen blends and obtained a selective permeability separation membrane with a microporous structure through cross-linking modification with genipin; the membrane has a high permeation flux (698L·m -2 ·h -1 ), the oil-water separation efficiency is over 98%. During the development process, CS oil-water separation membranes are usually blended with collagen (BBC) to increase the specific surface area and porosity, thereby improving the separation efficiency of oil-water mixtures. Although CS oil-water separation membranes have the advantages of antibacterial, environmental protection, degradability and good biocompatibility, their weak mechanical properties and poor structural stability limit their promotion and application; further technical optimization is needed to construct a biomass-based oil-water separation membrane material with excellent mechanical properties and strong stability.
[0004] Exogenous cross-linking agents can be used to precisely control the biological and physicochemical properties of bio-based materials and are an effective method for regulating the mechanical properties and stability of chitosan / collagen-based membranes. Currently, there are no reports on the use of proanthocyanidins (PA) and sodium tripolyphosphate (TPP) as cross-linking agents to improve the mechanical properties and thermal stability of chitosan / collagen-based oil-water separation membranes. Summary of the invention
[0005] The present invention provides a method and application for improving the mechanical properties and structural stability of a chitosan / collagen-based oil-water separation membrane. The molecular cross-linking technology among carboxymethyl chitosan (CS), natural bone collagen (BBC), and natural cross-linking agents proanthocyanidin (PA) and sodium tripolyphosphate (TPP) is utilized to optimize the molecular structure and physicochemical properties of a chitosan / collagen-based nanofiber gel, construct CS / BBC fibrils and prepare an edible oil-water separation membrane using the CS / BBC fibrils, thereby improving the mechanical properties and structural stability of the chitosan / collagen-based oil-water separation membrane and solving the problems existing in the prior art.
[0006] One of the technical solutions adopted by the present invention is:
[0007] A method for improving the mechanical properties and structural stability of a chitosan / collagen-based oil-water separation membrane comprises the following steps:
[0008] (1) Preparation of CS / BBC solution
[0009] Chitosan (CS) and collagen (BBC) were stirred and dissolved in acetic acid and 40mmol / L phosphate buffer to prepare 2mg / mL CS stock solution and 0.5mg / mL BBC stock solution respectively; centrifuged at 3000×g for 5min to remove undissolved solid particles;
[0010] The BBC stock solution was neutralized with NaOH to neutrality (pH 7.2±0.2), and an equal volume of the CS stock solution was taken and mixed and adjusted to pH 7.4, so that the stoichiometric ratio (w / w) of BBC and CS reached 4:1; after mixing, the mixture was stirred at a low speed in a chromatography cabinet at 4°C to obtain a CS / BBC solution; and the solution was set aside;
[0011] (2) Preparation of CS / BBC-based gel separation membrane
[0012] Select a 300-mesh stainless steel mesh, and perform ultrasonic cleaning with anhydrous ethanol and a 0.1 mol / L hydrochloric acid solution in sequence, and wash the hydrochloric acid on the surface of the stainless steel mesh with deionized water to obtain a stainless steel mesh membrane; soak the stainless steel mesh membrane in the CS / BBC solution prepared in step (1) for 5 min-10 min, then take it out, keep it at 30° C. for 24 h-36 h, form a CS / BBC-based fiber gel on the surface of the stainless steel mesh by self-assembly, and dry it at room temperature to obtain a CS / BBC-based gel separation membrane sample (CS / BBC);
[0013] (3) Preparation of cross-linked CS / BBC-based oil-water separation membrane
[0014] PA and TPP are respectively dissolved in phosphate buffer to a concentration of 10 mg / mL; the CS / BBC-based gel separation membrane sample obtained in step (2) is immersed in PA, or TPP, or first PA and then TPP at room temperature for a certain period of time to complete the cross-linking treatment; each cross-linked sample is washed in 96%, 70% and 50% ethanol solutions in turn, and finally washed with distilled water for multiple times; after drying at room temperature, a PA-crosslinked CS / BBC-based oil-water separation membrane CS / BBC / P, a TPP-crosslinked CS / BBC-based oil-water separation membrane CS / BBC / T, or a PA+TPP-crosslinked CS / BBC-based oil-water separation membrane CS / BBC / PT is obtained.
[0015] Furthermore, in step (1), the acetic acid concentration is 0.5 mol / L, the pH of the phosphate buffer is 7.4; the centrifugation condition is 3000×g for 5 min; the NaOH concentration is 10 mol / L; and low-temperature and low-speed stirring refers to low-speed stirring and mixing in a chromatography cabinet at 4°C.
[0016] Furthermore, in step (1) of preparing the CS stock solution, chitosan is dissolved in 0.5 mol / L acetic acid by stirring in a chromatography cabinet at 4°C.
[0017] In step (2), the concentration of the hydrochloric acid solution is 0.1 mol / L; the ultrasonic cleaning conditions are 20-30 kHz, 1 hour; and the room temperature drying period is 2 days.
[0018] Furthermore, in step (3), the CS / BBC-based gel separation membrane sample is immersed in different cross-linking agents at room temperature and the operation is divided into the following three types:
[0019] Soak in PA for 2 hours only, soak in TPP for 2 hours only, or soak in PA for 1 hour first and then soak in TPP for 1 hour. Preferably, the above operation is: soak in PA for 1 hour first and then soak in TPP for 1 hour.
[0020] Furthermore, in step (3), the mixture was washed in ethanol solution at different concentrations for 10 min; washed in distilled water for 3 times, each time for 10 min; and dried at room temperature for 2 days.
[0021] Furthermore, in step (3), the concentration of the phosphate buffer is 40 mmol / L and the pH is 7.4.
[0022] A chitosan / collagen-based oil-water separation membrane is prepared by the method described above.
[0023] The second technical solution adopted by the present invention is:
[0024] The chitosan / collagen-based oil-water separation membrane prepared by the above method is used in the treatment of oily wastewater in the food industry processing field.
[0025] Beneficial effects of the present invention:
[0026] The present invention adds exogenous cross-linking agents proanthocyanidins (PA) and / or sodium tripolyphosphate (TPP), which can cross-link and improve the microstructure of chitosan / collagen-based oil-water separation membranes, making their cross-linking degree and structural order higher. Scanning electron microscopy shows that CS / BBC / P (98.3%, 136μm) and CS / BBC / PT (96.5%, 175μm) have higher porosity than CS / BBC / T (94.8%, 203μm), but smaller pore size. Compared with CS / BBC-based gel oil-water separation membranes, the addition of PA and TPP produces hydrogen bond cross-linking with BBC and ionic cross-linking with phosphate groups and amino groups of CS, thereby improving the mechanical strength, mechanical properties and thermal stability of chitosan / collagen-based oil-water separation membranes to varying degrees, providing a reference for improving the performance of chitosan / collagen-based oil-water separation membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 FTIR analysis of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0028] Figure 2 XRD analysis of CS / BBC-based gel separation membrane before and after cross-linking with PA and PTT;
[0029] Figure 3 The SEM microstructure of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0030] Figure 4 Differential scanning calorimetry analysis of CS / BBC-based gel separation membrane before and after cross-linking with PA and PTT;
[0031] Figure 5 Thermogravimetric analysis of CS / BBC (A), CS / BBC / P (B), CS / BBC / T (C), and CS / BBC / PT (D) separation membranes;
[0032] Figure 6is the cross-linking degree of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0033] Figure 7 is the swelling ratio of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0034] Figure 8 is the water retention rate of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0035] Fig. 9 is the solubility of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0036] Fig.10 The enzymatic resistance of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0037] Fig.11 The stress-strain curves of CS / BBC-based gel separation membrane before and after PA and PTT cross-linking;
[0038] Fig.12 This is a typical cross-section of the stress-strain curve of the CS / BBC / PT-based gel separation membrane.
[0039] in, Figure 3 A in the middle is the SEM microstructure of freeze-dried CS / BBC, B is the SEM microstructure of CS / BBC / P, C is the SEM microstructure of CS / BBC / T, and D is the SEM microstructure of CS / BBC / PT;
[0040] Figure 4 The horizontal axis is temperature / ℃; the vertical axis is heat flow / W*g-1;
[0041] Figure 5 The middle abscissa is temperature / ℃, the left ordinate is weight loss / %, the right ordinate is mass loss rate / %*℃-1; Figure 5 A is the thermogravimetric analysis of CS / BBC separation membrane, B is the thermogravimetric analysis of CS / BBC / P separation membrane, C is the thermogravimetric analysis of CS / BBC / T separation membrane, and D is the thermogravimetric analysis of CS / BBC / PT separation membrane. DETAILED DESCRIPTION
[0042] In order to clearly illustrate the technical features of this solution, the present invention is described in detail below through specific implementation methods and in conjunction with the accompanying drawings. The scope of the present invention is not limited to the following embodiments. Professionals in the field can understand that various changes and modifications can be made to the present invention without departing from the spirit and scope of the present invention.
[0043] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0044] The present invention provides a method for improving the mechanical properties and structural stability of a chitosan / collagen-based oil-water separation membrane. The method utilizes the molecular cross-linking technology between carboxymethyl chitosan (CS), natural bone collagen (BBC), and natural cross-linking agents proanthocyanidin (PA) and sodium tripolyphosphate (TPP), optimizes the molecular structure and physicochemical properties of chitosan / collagen-based nanofiber gel, constructs CS / BBC fibrils and prepares an edible oil-water separation membrane based on them, thereby improving the mechanical properties and structural stability of the chitosan / collagen-based oil-water separation membrane.
[0045] Example 1
[0046] A method for improving the mechanical properties and structural stability of a chitosan / collagen-based oil-water separation membrane comprises the following steps:
[0047] (1) Preparation of CS / BBC solution
[0048] Chitosan (CS) and collagen (BBC) were stirred and dissolved in 0.5 mol / L acetic acid (operated in a 4℃ chromatography cabinet) and 40 mmol / L phosphate buffer (PBS, pH 7.4) to prepare 2 mg / mL CS stock solution and 0.5 mg / mL BBC stock solution; centrifuged at 3 000×g for 5 min to remove undissolved solid particles. The BBC stock solution was neutralized to neutrality (pH 7.2±0.2) with 10 mol / L NaOH, and an equal volume of CS stock solution was taken and mixed and adjusted to pH 7.4, so that the BBC and CS reached the optimal stoichiometric ratio (w / w) of 4:1. After mixing, stir at low speed in a 4℃ chromatography cabinet to obtain a CS / BBC solution.
[0049] (2) Preparation of CS / BBC-based gel separation membrane
[0050] A 300-mesh stainless steel mesh (3 cm×3 cm) was selected, and ultrasonically cleaned with anhydrous ethanol and a 0.1 mol / L hydrochloric acid solution (20-30 kHz, 1 h) in sequence, and the hydrochloric acid on the surface of the stainless steel mesh was washed off with deionized water to obtain a stainless steel mesh membrane; the stainless steel mesh membrane was soaked in the CS / BBC solution prepared in step (1) for 5 min, and kept at 30°C for 24 h, and a CS / BBC-based fiber gel was formed on the surface of the stainless steel mesh by self-assembly, and dried at room temperature for 2 days to obtain a CS / BBC-based gel separation membrane (CS / BBC).
[0051] (3) Preparation of CS / BBC / PT oil-water separation membrane
[0052] PA and TPP were dissolved in 40mmol / L phosphate buffer (PBS, pH 7.4) to a concentration of 10mg / mL (1%). The CS / BBC fibril gel mesh (i.e., the CS / BBC-based gel separation membrane sample obtained in step (2)) was first soaked in 1% PA for 1 hour at room temperature (25°C), and then continued to be soaked in 1% TPP for 1 hour. After cross-linking treatment, the sample was washed in 96%, 70% and 50% ethanol solutions (v / v) for 10 minutes each, and finally washed with distilled water for 3 times (10 minutes each time). After drying at room temperature for 2 days, the PA+TPP cross-linked CS / BBC-based oil-water separation membrane sample CS / BBC / PT was obtained.
[0053] Example 2
[0054] The preparation operation of the method of this embodiment is the same as that of embodiment 1, except that in step (3), the CS / BBC fibril gel membrane (i.e., the CS / BBC-based gel separation membrane sample obtained in step (2)) is immersed in 1% PA at room temperature (25° C.) for 2 h for cross-linking treatment.
[0055] This embodiment finally prepared the PA cross-linked CS / BBC based oil-water separation membrane sample CS / BBC / P
[0056] Example 3
[0057] The preparation operation of the method of this embodiment is the same as that of Example 1, except that in step (3), the CS / BBC fibril gel membrane (i.e., the CS / BBC-based gel separation membrane sample obtained in step (2)) is cross-linked by immersing it in 1% TPP at room temperature (25°C) for 2 hours.
[0058] This embodiment finally prepared the TPP cross-linked CS / BBC based oil-water separation membrane sample CS / BBC / T.
[0059] The following tests were performed on the CS / BBC based oil-water separation membrane sample CS / BBC / PT, the PA cross-linked CS / BBC based oil-water separation membrane sample CS / BBC / P, and the TPP cross-linked CS / BBC based oil-water separation membrane sample CS / BBC / T prepared by the method of the present invention.
[0060] 1. Testing the effect of cross-linking on the molecular structure of CS / BBC-based gel separation membranes
[0061] 1.1 Fourier transform infrared spectroscopy (FTIR) was performed on the samples to evaluate the molecular structure changes caused by cross-linking. The scanning range was 4000-500 cm -1, resolution 1cm -1 .
[0062] FTIR analysis showed that all samples, including BBC, showed five characteristic bands of collagen, namely, amide A band (3440-3400 cm -1 ), amide B band (2 980~2 850cm -1 ), amide I band (1 700~1600cm -1 ), amide II band (1 600~1 550cm -1 ) and amide III band (1360~1200cm -1 ), only the intensity and position of the bands after cross-linking have changed, see Figure 1 The results showed that the cross-linking of CS / BBC-based fibril gel (i.e., CS / BBC-based gel separation membrane sample) by PA / TPP did not change the characteristic structure of collagen at the molecular level. The amide A peak originated from the NH stretching vibration and was very sensitive to the typical triple helix structure of collagen, usually located at 3440-3400 cm -1 However, when the NH group participates in hydrogen bonding, its position shifts to a lower frequency (red shift), about 3 300 cm -1 The lower wavenumbers indicate that more NH groups are involved in hydrogen bonding. The amide A bands of BBC, CS / BBC, CS / BBC / P, CS / BBC / T, and CS / BBC / PT appear at 3325, 3305, 3380, 3280, and 3285 cm-1, respectively. -1 The results show that the cross-linking based on PA strengthens the hydrogen bonding in the CS / BBC-based fibril gel, while the cross-linking based on TPP destroys the hydrogen bonding in the CS / BBC-based fibril gel to a certain extent. In addition, the amide B band (CH2 asymmetric stretching) and amide I band (C=O stretching vibration) of CS / BBC / P, CS / BBC / T and CS / BBC / PT all shift to higher wavenumbers (blue shift) after cross-linking, indicating that the cross-linking treatment may cause the N-terminal free NH3 + The exposure of the groups increased, and the spatial structural order of the CS / BBC fibril gel was also enhanced by the participation of the C=O groups in cross-linking. The amide II band of CS / BBC / P also showed a slight blue shift, which was attributed to the NH bending and CN stretching vibrations, while the amide II band of CS / BBC / T did not undergo an obvious blue shift, which indicated that more amino groups may participate in the cross-linking of PA (hydrogen bonding), and its cross-linking degree may be higher, thus the molecular regularity is higher. The characteristic absorption range of the amide III band is 1 200-1 360cm -1, which is the combined peak of CN stretching vibration and NH deformation of amide bond, as well as the absorption caused by the swinging vibration of proline side chain and glycine skeleton CH2; all samples have significant amide III band, which proves that the BBC in all samples maintains a complete triple helix structure, and cross-linking does not have a significant effect on the triple helix structure of BBC.
[0063] 1.2 X-ray diffraction scans were performed on the samples to evaluate the changes in the crystal structure caused by the crosslinker. An XRD diffractometer (XRD-6000, Shimadzu, Kyoto, Japan) was used with slight modifications, using copper Kα as the X-ray source: scanning range 5–60° (2θ); scanning speed 2° / min.
[0064] See also Figure 2 , the XRD spectrum of CS / BBC-based gel separation membrane shows two main diffraction peaks. The first peak is a sharp peak at 2θ (the angle between the incident X-ray and the diffraction line) of about 8°, reflecting the BBC fiber crystal structure inside the gel separation membrane. The high-intensity diffraction peak here indicates that the CS / BBC-based gel separation membrane formed after cross-linking of PA, TPP and PA+TPP through covalent bonds, ionic bonds or hydrogen bonds has a greater degree of crystallinity. Compared with BBC and CS / BBC fiber gel samples, the intensity of the diffraction peak of the cross-linked CS / BBC-based gel sample is significantly greater, indicating that the cross-linking of PA and TPP induces a higher degree of crystallinity. CS / BBC / P has the largest peak intensity and the highest degree of crystallinity, indicating that stronger hydrogen bonding is more conducive to the formation of a crystal structure. The second broad peak 2θ is at 19°-21°, which comes from the diffuse scattering of the non-crystalline area. After the CS / BBC fiber gel is cross-linked, the diffraction angle increases, and according to the Bragg law, the non-crystalline area decreases. In addition, the right shift of 2θ indicates that cross-linking makes the CS / BBC fibril gel more ordered. Some reflection peaks with smaller intensity in CS / BBC fiber gel decreased in intensity after the introduction of PA and TPP, indicating that the integrity of the cross-linked CS / BBC-based gel separation membrane increased. The XRD pattern of the CS / BBC / P group was relatively smoother, indicating that the cross-linking degree and structural order of the CS / BBC / P-based gel separation membrane under the action of PA were higher, and the cross-linking efficiency of PA for CS / BBC-based gel separation membrane was better than that of TPP.
[0065] 2. Testing the effect of cross-linking on the pore structure of CS / BBC-based gel separation membranes
[0066] See also Figure 3, SEM observed that the three CS / BBC-based gel separation membranes all had isotropic porous multilayer sheet-like stacking structures. The average pore size and porosity of the CS / BBC-based gel separation membranes are shown in Table 1. All CS / BBC-based gel separation membrane samples are highly porous structures with porosities between 93–99% and pore sizes concentrated in 130–270 μm. Among them, CS / BBC / P (98.3%, 136 μm) and CS / BBC / PT (96.5%, 175 μm) have higher porosity than CS / BBC / T (94.8%, 203 μm), but smaller pore sizes. This may be due to the higher degree of crosslinking of PA to CS / BBC fibril gel, which destroys the three-dimensional structure generated by CS / BBC self-crosslinking, thus making the structures of CS / BBC / P and CS / BBC / PT more ordered, resulting in more but relatively smaller pores. The porosity index is also affected by crosslinking to a certain extent. The crosslinking agent causes the volume shrinkage of the overall sample by crosslinking with each other, and the structure is more compact. In addition, the mass of CS / BBC fibril gel will also change after cross-linking. PA and TPP will bind to the positively charged protonated amino groups of CS / BBC through hydroxyl groups and negatively charged phosphate ions, respectively, to establish hydrogen bonds or ionic interactions, which will increase its mass. The mass change will also cause changes in porosity and pore size (Table 1).
[0067] Table 1 Morphological characteristics of CS / BBC-based gel separation membranes before and after different cross-linking
[0068]
[0069] 3. Test the effect of cross-linking on thermal stability
[0070] Thermal stability is an important indicator for evaluating the stability of bio-based oil-water separation membranes during use. Figure 4As shown in the figure, the peak temperature and peak area of the thermal denaturation induced by heating in the DSC curve represent the melting temperature (Tm) of the sample and the enthalpy change energy (ΔH) required to destroy the sample structure, respectively. The melting temperature Tm of BBC is 51.3°C and ΔH is 3.11J / g. After CS and BBC are blended, the Tm is increased to 55.6°C and the ΔH is increased to 7.26J / g. The possible reason is that CS enhances the hydrogen bonding effect between the collagen skeleton, thereby enhancing the thermal stability of the CS / BBC fibril gel. With the cross-linking of PA and TPP, its thermal stability (60.6-66.8°C, 11.71-15.52J / g) is further enhanced, expanding the application range of CS / BBC-based oil-water separation membranes. Among them, CS / BBC / P (66.8℃, 15.52J / g) and CS / BBC / PT (62.2℃, 13.26J / g) have stronger thermal stability than CS / BBC / T (60.6℃, 11.71J / g). Combined with the results of FTIR / XRD spectroscopy, it is speculated that this may be due to the stronger hydrogen bonding mediated by the large number of hydroxyl groups of PA and the better cross-linking effect, resulting in higher Tm and ΔH.
[0071] like Figure 5As shown in the figure, with the increase of temperature, the CS / BBC-based gel separation membrane samples all showed three different weight loss stages. The first weight loss stage was related to the escape of free water in the sample system and the destruction of the hydrogen bonds between collagen chains shown in FTIR; the mass loss of CS / BBC / P (4.31%), CS / BBC / T (3.19%) and CS / BBC / PT (6.92%) was smaller than that of CS / BBC (7.69%), which may be due to the high hydrogen bonding between PA and free water, which can better prevent the escape of free water. At the same time, it was observed that the temperature (DTG) at which the mass loss of the samples in the first stage was the fastest was lower for the cross-linked CS / BBC-based gel separation membrane samples (115.56-133.43℃) than that of the CS / BBC fibril gel (145.05℃), which may be due to the introduction of the cross-linking agent that destroyed the cross-linking hydrogen bonds between collagen chains. The second weight loss stage released part of the bound water in the sample system and small molecular products such as peptides and amino acids produced after the thermal degradation and cleavage of peptide bonds. Similarly, the temperature at which the mass loss of the samples in the second stage was fastest was observed to be higher for the cross-linked CS / BBC based gel separation membrane samples (293.65-311.23°C) than for the CS / BBC fibril gel (293.11°C). The third stage of thermal degradation further decomposed the peptides and amino acids into CO2, CO and NO by high temperature deamination (destruction of peptide bonds) and dehydration (destruction of CN and CO bonds). At 500°C, the original mass of the final residual part of each sample was: CS / BBC (29.3%), CS / BBC / P (33.9%), CS / BBC / T (30.95%) and CS / BBC / PT (33.35%). From the results of TGA / DTG, it can be seen that the cross-linking of PA, TPP and PA+TPP has no obvious positive effect on the thermal stability of CS / BBC fibril gel at high temperature. The possible reason is that the cross-linking of PA and TPP makes the fibril structure denser and increases the crystal order; however, the introduction of the cross-linking agent also destroys the original intra-chain and inter-chain hydrogen bonds of collagen, resulting in insufficient adjacent amino or carboxyl groups, and failing to form a sufficient number of stable amide bonds, which has a negative impact on its thermal stability.
[0072] 4. Effects of P and TPP on the cross-linking degree of CS / BBC-based gel separation membranes
[0073] Depend on Figure 6 It can be seen that the cross-linking efficiency of PA is better than that of TPP: CS / BBC / P (46.53%), CS / BBC / PT (30.61%) and CS / BBC / T (38.96%). PA shows a higher saturated cross-linking degree, which may be related to the reaction of active groups such as amino and carboxyl groups in CS / BBC with a large number of hydroxyl groups in PA. Cross-linking agents can inhibit the formation of collagen fibers and have a negative impact on their mechanical strength. Therefore, excessive cross-linking should be avoided during the preparation process.
[0074] 5. Test the effect of cross-linking on swelling rate and water retention rate
[0075] The swelling property reflects the ability of the gel material to absorb liquid, which is related to its molecular microstructure and hydrophilicity (hydrophilic group level). Figure 7 It can be seen that all samples showed obvious swelling in a short period of time and then gradually reached equilibrium. Under equilibrium, CS / BBC / P showed the highest swelling rate (about 68 times), while CS / BBC / PT and CS / BBC / T were 45 times and 36 times, respectively. The water retention rate also showed a similar trend, such as Figure 8 , CS / BBC / P, CS / BBC / PT, and CS / BBC / T showed approximately 7, 4.4, and 5.3 times their initial weight, respectively. This indicates that crosslinking of PA, TPP, and PA+TPP improves the swelling properties of CS / BBC fibril gels, while CS / BBC / P has a higher degree of crosslinking, further revealing that the higher the degree of crosslinking of CS / BBC fibril gels, the higher their swelling rate. The reason for this is mainly related to the composition (hydrophilic groups) of the CS / BBC gel separation membrane and the compact microstructure formed by crosslinking. A higher degree of crosslinking provides a more stable medium retention property. The gradual increase in swelling capacity and water retention capacity during the culture process may be the result of pillar expansion, which leads to a loosening of the polymer network and increases its overall swelling capacity. Crosslinking is essential for the swelling capacity and water retention capacity of hydrogels because the crosslinking formed by the addition of PA and PT crosslinkers has a higher level of stability compared to the self-crosslinking of collagen and CS. This experiment also observed that the CS / BBC fibril gel as a whole did show a higher swelling rate (about 25 times) and water retention (about 2.9 times), which may be due to the good hydrophilicity of CS. However, the lack of structural strength of the CS / BBC fibril gel will lead to pore collapse, thus limiting the further improvement of its swelling rate and water retention.
[0076] 6. Testing the effect of cross-linking on solubility
[0077] Bio-based oil-water separation membranes need to maintain their structural integrity during use without causing significant dissolution. Fig. 9It can be seen that all samples showed a gradually increasing weight loss after immersion and dissolution, and the weight loss tended to balance after the 10th day. The non-cross-linked CS / BBC fibril gel showed a significantly higher weight loss (about 55.6%), that is, a higher solubility. CS / BBC / PT and CS / BBC / T showed similar solubility levels (31.6% and 35.9%), while CS / BBC / P had the lowest solubility (17.3%). It can be seen that further cross-linking treatment with PA and TPP enhanced the structural stability of the CS / BBC-based oil-water separation membrane, thereby improving its dissolution resistance. The dissolution resistance of CS / BBC / P and CS / BBC / PT is better than that of CS / BBC / T, which may be because the polypeptide chain of BBC or the sugar chain of CS is more inclined to act with PA, and a higher degree of cross-linking leads to better dissolution resistance.
[0078] VII. Testing the effect of cross-linking on in vitro enzymatic resistance
[0079] Some food processing wastewater has protease activity, which may catalyze the hydrolysis of collagen in oil-water separation membranes, thereby affecting the separation effect and service life of the separation membranes. Therefore, the effect of cross-linking on in vitro enzymatic resistance was analyzed. Fig.10 As shown in the figure, the degradation degree of all separation membrane samples increased with time and eventually stabilized, but the resistance of CS / BBC fibril gel was the worst. This may indicate that the connection between the polyelectrolyte complex formed by the enzymatic hydrolysis of CS / BBC and the residual free amine / carboxyl groups of BBC is not strong enough or / and the position (quantity) of these ionic bonds is not enough to form a high-density protective network after treatment. After 14 days of in vitro enzymatic hydrolysis, the degradation degrees of CS / BBC, CS / BBC / P, CS / BBC / PT and CS / BBC / T were 35.2%, 11.1%, 20.6% and 23.2%, respectively. The degradation rates of CS / BBC / P and CS / BBC / PT were lower than those of CS / BBC / T, which means that PA has a better cross-linking effect on CS / BBC than TPP. The results show that cross-linking enhances resistance to protease action, and in vitro enzymatic resistance is proportional to the degree of cross-linking. In summary, PA, TPP and PA+TPP blocked the cleavage sites of proteases and improved the in vitro protease resistance by enhancing the cross-linking and structural integrity of CS / BBC fibril gels.
[0080] 8. Testing the effect of cross-linking on separation efficiency and flux
[0081] Flux and separation performance are the most important factors that determine the application potential of CS / BBC-based gel separation membranes. The experimental results of oil-water separation prepared under different conditions of the present invention are shown in Table 2. The separation efficiency of the CS / BBC fibril gel separation membrane is 97.16%. The separation efficiency after cross-linking is reduced to varying degrees. The separation efficiencies of CS / BBC / P, CS / BBC / T, and CS / BBC / PT are 95.41%, 91.66%, and 93.86%, respectively, all exceeding 90%, meeting the use requirements of biomass-based oil-water separation membranes. Compared with sodium tripolyphosphate (TPP), proanthocyanidins (PA) have a greater effect on the flux of the separation membrane. The flux of the CS / BBC fibril gel separation membrane is 10638 L·m -2 ·h -1 , CS / BBC / T flux is 10224L·m -2 ·h -1 , while the flux of CS / BBC / P is only 6643 L·m -2 ·h -1 The possible reason is that cross-linking causes the BBC on the membrane surface to agglomerate, blocking the effective pores on the membrane surface, resulting in a decrease in flux. When PA and TPP are used simultaneously, the flux is 9987 L·m -2 ·h -1 , which has little effect on the separation membrane flux.
[0082] Table 2 Effects of different cross-linking on flux and separation performance
[0083]
[0084] IX. Testing the effect of cross-linking on mechanical strength
[0085] Mechanical strength (such as Young's modulus and compressive strength) directly affects the application potential of biomass-based oil-water separation membranes in the food industry. Therefore, the development of gel separation membrane materials with sufficient mechanical properties is the biggest challenge. Fig.11 The stress-strain curves of CS / BBC fibril gel and CS / BBC are shown, and the Young's modulus calculated from the initial part of these curves is shown in Table 3. The elastic modulus values of the cross-linked CS / BBC-based gel separation membrane (10.2-12.5 kPa) were significantly improved compared to the CS / BBC fibril gel (5.6 kPa). The cross-linking of PA and TPP significantly improved the compressive resistance of the CS / BBC-based gel separation membrane, confirming that cross-linking can increase the stiffness of the polymer matrix by introducing additional connections in the polymer network and enhance its resistance to dimensional changes.
[0086] Table 3 Effect of different cross-linking on the mechanical strength of CS / BBC-based gel separation membrane
[0087]
[0088] At the same time, in order to evaluate the performance of the cross-linked CS / BBC-based gel separation membrane under continuous extrusion, the same sample was tested at least three times. The composite cross-linked CS / BBC-based oil-water separation membrane sample CS / BBC / PT of Example 1 with relatively better comprehensive performance indicators was selected as an example. After continuous compression, the cross-section of the sample did not change significantly (in all strain ranges, the curves almost overlapped with each other), indicating that it has good structural recovery ability. The possible reason is that the external cross-linking introduced by PA and TPP provides good stiffness. The results are shown in Fig.12 .
[0089] The above specific implementation manner cannot be used as a limitation on the protection scope of the present invention. For those skilled in the art, any substitution, improvement or change made to the implementation manner of the present invention falls within the protection scope of the present invention.
[0090] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membranes, characterized in that: The steps are as follows: (1) Preparation of CS / BBC solution Chitosan CS and collagen BBC were stirred and dissolved in acetic acid and phosphate buffer respectively to prepare 2 mg / mL CS stock solution and 0.5 mg / mL BBC stock solution; Centrifuge to remove undissolved solid particles; The BBC stock solution was neutralized with NaOH to neutrality, and an equal volume of CS stock solution was taken and mixed and adjusted to pH 7.4 to achieve a 4:1 stoichiometric ratio of BBC to CS; After mixing, stir at low temperature and low speed to mix evenly to obtain CS / BBC solution for later use; (2) Preparation of CS / BBC-based gel separation membrane A 300-mesh stainless steel mesh is selected, and ultrasonic cleaning is performed with anhydrous ethanol and a hydrochloric acid solution in sequence, and the hydrochloric acid on the surface of the stainless steel mesh is washed off with deionized water to obtain a stainless steel mesh membrane; the stainless steel mesh membrane is soaked in the CS / BBC solution prepared in step (1) for 5 to 10 minutes, and then taken out and kept at 30° C. for 24 to 36 hours to form a CS / BBC-based fiber gel on the surface of the stainless steel mesh by self-assembly, and dried at room temperature to obtain a CS / BBC-based gel separation membrane sample; (3) Preparation of cross-linked CS / BBC-based oil-water separation membrane Dissolve PA and TPP in phosphate buffer respectively to a concentration of 10 mg / mL; soak the CS / BBC-based gel separation membrane sample obtained in step (2) in PA, or TPP, or PA first and then TPP for a certain period of time at room temperature to complete the cross-linking treatment; After cross-linking, each sample was washed in ethanol solutions of different concentrations in turn, and finally washed multiple times with distilled water; after drying at room temperature, PA cross-linked CS / BBC based oil-water separation membrane CS / BBC / P, TPP cross-linked CS / BBC based oil-water separation membrane CS / BBC / T, or PA+TPP cross-linked CS / BBC based oil-water separation membrane CS / BBC / PT was obtained.
2. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: In step (1), the acetic acid concentration is 0.5 mol / L, the pH of the phosphate buffer is 7.4; the centrifugation condition is 3000×g for 5 min; the NaOH concentration is 10 mol / L; and the low-temperature and low-speed stirring refers to low-speed stirring and mixing in a chromatography cabinet at 4° C.
3. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: In step (2), the concentration of the hydrochloric acid solution is 0.1 mol / L; the ultrasonic cleaning conditions are 20-30 kHz, 1 hour; and the room temperature drying period is 2 days.
4. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: Step (3) The CS / BBC-based gel separation membrane samples were immersed in different cross-linking agents at room temperature and operated in the following three ways: Soak in PA only for 2 h, soak in TPP only for 2 h, or soak in PA for 1 h and then soak in TPP for 1 h.
5. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 4, characterized in that: Step (3) The CS / BBC-based gel separation membrane sample was immersed in different cross-linking agents at room temperature: first immersed in PA for 1 hour, and then immersed in TPP for 1 hour.
6. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: In step (3), the volume concentrations of the ethanol solutions used for washing each sample after cross-linking are 96%, 70% and 50% respectively, and washing is performed for 10 minutes at each concentration.
7. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: Step (3) Wash with distilled water for 3 times, each time for 10 min; and dry at room temperature for 2 days.
8. The method for improving the mechanical properties and structural stability of chitosan / collagen-based oil-water separation membrane according to claim 1, characterized in that: The concentration of the phosphate buffer in step (3) is 40 mmol / L and the pH is 7.
4.
9. A chitosan / collagen-based oil-water separation membrane, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Application of the chitosan / collagen-based oil-water separation membrane prepared according to any one of the methods of claims 1 to 8 in the treatment of oily wastewater in the food industry processing field.
Citation Information
Patent Citations
Preparation method of mulberry fiber composite three-dimensional oil-water separation membrane
CN112717472A
Anthocyanidin-loaded collagen eye mask as well as preparation method and application thereof
CN117562875A